THE DAMAGE OF THE OPTIC NERVE AS THE OUTCOME OF UNINTENTIONAL POISONING BY CLOSANTEL - Kurakina, Evgenia Sergeevna; Ioyleva, Elena Eduardovna; Saif, Mutlaq Ali Saif; Gavrilova, Natalia Alexandrovna (MNJ (Malang Neurology Journal), 2021)
Background: In recent decades, the problem of toxic damage of the visual system due to poisoning by various medicines has become particularly relevant. The clinical case of a bilateral acute optic neuropathy of toxic genesis in a patient by the unintentional application of closantel used in veterinary practice is presented in the report. Closantel is a structural derivative of the salicylanilides, which is used exclusively in veterinary medicine for the prevention and treatment of large and small-scale cattle. Neurological and ophthalmic symptoms are often associated with the intoxication of closantel.Objective: To describe the toxic damage of the optic nerve due to unintentional poisoning by closantel.Methods: A patient aged 55 years is examined. A standard survey of ophthalmology was carried out. Photoregistration of the ocular fundus was used by a funduscamera Visucam 500 (Carl Zeiss Meditec AG, Germany), from special methods of research - the spectral optical coherence tomography (OCT) with a study of the macular area of the retina and the disc of the optic nerve on the device Zeiss Cirrus 5000 (Carl Zeiss Meditec, USA) and the optical coherence tomography with the function of angiography (OCT-A) of the macular area of the retina using RTVue XR Avanti (Optovue, USA)Results: The patient complained of a severe, yet painless, reduction in vision of both eyes after an accidental intramuscular injection of the medicine called "Closantrem" in dose 4.0 ml. The visual acuity OU - an accounting of fingers on the face at a distance of 10 cm. By ophthalmoscopy OU: the disc of the optic nerve is discolourated, its boundaries are indistinct, the arteries and the veins are narrowed, in the macular area of the retina without a visible physical pathology. The perimetry is in the correct projection of the light. A reduction in the thickness of the external and internal layers of the retina was observed as a result of the OCT of the macular zone OU. According to OCT of the disc of the optic nerve: the thickness of the layer of nerve fibres is in the upper and lower nasal segments. OS – the prominence of the disc of the optic nerve in vitreous. The fascinated changes of the cerebral cortex have not been found during the MRT. The diagnosis was made OU: Acute optic neuropathy of toxic genesis. A course of integrated conservative treatment has been introduced: the anti-inflammatory, metabolic, nootropic, vitamin therapy, magnetotherapy, electrostimulation and electrophoresis.Conclusion: Potentially, any medicines are toxic, which may cause a number of side effects from the visual and central nervous system. The toxic damage of the ganglion cells of the retina was initially occurring due to unintentional application of closantel, resulting in a reduction of the central visual acuity, followed by the development of the optic nerve atrophy.